Work-family balance among employees in an international insurance company in Malaysia: an investigation on factors that affect work, family and life satisfaction - Chew, Le Huey (2019)
Achieving work-life balance has always been the main goal of most employees and organisations in the world and it is not easy. Work-life balance would affect employees and employers negatively if it is not achieved well. Having work-life balance would mean increasing the employees’ level of work satisfaction, family satisfaction and life satisfaction. When employees are satisfied, they would most likely perform well in the organisations which would lead to increased productivity. Therefore, work-life balance benefits both employees and employers and both parties should strive their best to maintain it.